2012
DOI: 10.3310/hta16150
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and validation of prediction rules for identifying children with serious infections in emergency departments and urgent-access primary care.

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(104 citation statements)
references
References 101 publications
2
89
0
13
Order By: Relevance
“…(18,19) We found that a low blood eosinophil count (≤ 50 cells/mm 3 ) is similar to a high CRP level (≥1.22 mg/dL) and a high neutrophil count (>5100 cells/mm 3 ) for predicting bacterial infection in the pediatric emergency department. However, none of them had sufficient discriminatory power.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…(18,19) We found that a low blood eosinophil count (≤ 50 cells/mm 3 ) is similar to a high CRP level (≥1.22 mg/dL) and a high neutrophil count (>5100 cells/mm 3 ) for predicting bacterial infection in the pediatric emergency department. However, none of them had sufficient discriminatory power.…”
Section: Discussionmentioning
confidence: 95%
“…C-reactive protein (CRP) and the leukocyte and neutrophil counts are the acute-phase reactants used most widely in children admitted to the emergency department with a high fever. (1)(2)(3) In the last 20 years, procalcitonin has been identified as a promising bacterial infection marker in children with fever. Also, CD 15s as a neutrophil surface molecule was reported a potentially valuable biomarker in infants with severe bacterial infection.…”
Section: Introductionmentioning
confidence: 99%
“…13 The YOS has been validated in follow-up studies. 14,16 A convenience sample of children aged 2 months to 18 years presenting with respiratory symptoms (eg, cough, dyspnea, wheezing) were evaluated by using the Respiratory Observation Checklist (Fig 2). This tool, developed specifically for the present study by the authors, is a checklist of common observational signs of respiratory distress.…”
Section: Methodsmentioning
confidence: 99%
“…However, previous studies evaluating the role of observation in assessing febrile children and children in respiratory distress have validated observation as both predictive and reliable in identifying underlying serious illness. [13][14][15][16] The purpose of the present study was to determine the interobserver reliability of telemedicine observations, compared with bedside observations, in assessing febrile children and children in respiratory distress.…”
mentioning
confidence: 99%
“…While recognition of septic shock may be relatively straightforward in the context of an intensive care unit that deals with many such patients, it is much more challenging to ensure that early signs of septic shock are recognized in children initially presenting to healthcare services where such problems are much less frequent [21,22]. Studies of meningococcal disease suggest that while the ''full-blown'' picture may be easy to recognize, the clinical features in the early phase of the disease may be very non-specific and subtle [23].…”
Section: Recognitionmentioning
confidence: 99%